If it's not what You are looking for type in the equation solver your own equation and let us solve it.
4(4x-9)-6=4(x-4)+46
We simplify the equation to the form, which is simple to understand
4(4x-9)-6=4(x-4)+46
Reorder the terms in parentheses
+(+16x-36)-6=4*(x-4)+46
Remove unnecessary parentheses
+16x-36-6=+4+*(+x-4+)+46
Reorder the terms in parentheses
+16x-36-6=+(+4x-16)+46
Remove unnecessary parentheses
+16x-36-6=+4x-16+46
We move all terms containing x to the left and all other terms to the right.
+16x-4x=-16+46+36+6
We simplify left and right side of the equation.
+12x=+72
We divide both sides of the equation by 12 to get x.
x=6
| 16x^2-7t=17t-9 | | 36-6x=14+5x | | 2u^2+13u+15=0 | | (4x^2)+4x+(4y^2)-32y-335=0 | | 4x^2-147=0 | | (7/2)^-1=-1/7x | | (X-7)/2=(5-x)/4 | | 54-8x=18+10X | | 3(3x+5)=60 | | 8(3t-5)+12=-8 | | 54-8x=18+10 | | 16x^3-132x+252=0 | | 2+3(x+1)=9-3+2x | | 4(x+7)=-2x+34 | | x^3+8x^2+20x=0 | | 8x^2+5x+25=0 | | 5x+2=14+6X | | 13(17-x)=15(x+1) | | -7(1-2x)+8=-83 | | g(x)=3(5)x | | 4r^2-r+3=0 | | 3v+6=9-3(2v-2) | | x+3(x+6)=4(2x+1) | | 4(3z-3)=18 | | (2x-17)/5=-5 | | -11=3(v-7)-8v | | 13+x+2x=6x+1 | | 4x^2+8x+36=0 | | 73/100=81 | | 4x+4+8+2x=3(x+5) | | 3u^2+17u+24=0 | | 4x+6(x+2)=35 |